Analysis of Listening Skills in Elementary School: Narrative Literature Review - Aprianti Derlis; Nidya Chandra Muji Utami; Sri Yulianingsih; Renatalia Triningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
Listening skills are one of the four language skills, an internal activity in the human body through attentive listening. There are problems with listening comprehension in elementary school. This study aims to examine the issues in listening skills in elementary school with a Narrative Literature review research method and compare techniques. The stages of research are carried out by collecting, reducing, displaying articles, discussing, and drawing conclusions. Based on the results, there are 30 articles consisting of; 11 articles that discuss listening skills issues, 12 articles on the use of methods, models, and strategies in listening, and seven others discussing the use of instructional media as a solution to improve listening skills. The results showed that the problem of listening lies in the difficulty of students understanding the meaning of information presented orally, which is caused by the teacher's lack of ability to choose the right teaching tools and learning design.